Euthanasia dalam Tinjauan Hukum Pidana Perspektif KUHP Lama dan KUHP Baru (Undang-Undang Nomor 1 Tahun 2023) - Adinda Nadia Kusuma; Wulan Abidatul Khoiroh (Taruna Law: Journal of Law and Syariah, 2025)
Euthanasia is the process or act of killing someone who is sick or who suffers from an incurable disease. The act of euthanasia that has recently emerged due to the passage of Law No. 1 of 2023 concerning the New Criminal Code. Initially, euthanasia was regulated in the old criminal code book, precisely in Article 344. Due to the political reform of the criminal law on the above law, the criminal paradigm for euthanasia has also changed with Article 461 of the New Criminal Code. This research aims to understand the concept of euthanasia in the perspective of criminal law over the Old Criminal Code which is a product of colonizers and also the New Criminal Code over the latest Criminal Code Law along with the cases that occur. This research uses a normative legal research method using a conceptual approach and a legislative approach or known as The Statute Approach. The data used consisted of primary legal materials such as legal documents (laws) including the Criminal Code, as well as other related literature, while secondary legal materials were books, articles, journals, websites, and various other official sources related to the substance of euthanasia from the perspective of Criminal Law. The turmoil of the problem over euthanasia is the legality aspect, because positive law states that euthanasia is an illegal act. Not only that, the prohibition of euthanasia is also reviewed from a religious and moral perspective because euthanasia is a form of suicide (taking someone's life). The government must promote preventive measures to overcome the act of lethal injection. This is evidenced by the application for lethal injection on behalf of Berlin Silalahi at the Banda Aceh District Court.